PENERAPAN MODEL ELICITING ACTIVITIES (MEAs) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS XI MAN 4 PASAMAN BARAT - Roza, Melia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
This research is distributed-because there is some mathematical learning objectives have not been achieved one of mathematical communication ability. One of the factors the lack of mathematical communication skills, students are just listening to the teacher's explanation, then record and finish the matter practice. This, resulting in students ' knowledge and understanding of the information provided is limited to the teacher. An effort to do that is by applying Model Eliciting Activities (MEAs). The purpose of this research is to find out whether the mathematical communication skills of students by using Model Eliciting Activities (MEAs) better than mathematical communication skills of students by using conventional learning class XI IPS MAN 4 West Pasaman Barat. This type of research was quasi Experimental research. Sampling is done using Random Sampling techniques so that selected as experimental class is grade XI IPS 1 and as the control class is the grade XI IPS 2. Data analysis was performed using t-test with α = 0.05 level obtained thitung= and ttabel = 1,669 so > This berarti deny thus, it can be concluded that the mathematical communication skills of students by using Model Eliciting Activities (MEAs) better than mathematical communication skills of students using learning conventional in class XI IPS MAN 4 West Pasaman Barat